Damage characterization of composite plates under low velocity impact using ultrasonic guided waves. (1st April 2018) - De Luca, A.; Caputo, F.; Sharif Khodaei, Z.; Aliabadi, M.H.
Abstract: In this work, two numerical procedures based on Finite Elements Method (FEM) have been developed in order to simulate the Lamb wave propagation in Low Velocity Impact (LVI) damaged CFRP (Carbon Fibre Reinforced Polymer) laminate. The former (softening representation), usually adopted in literature, consists of modelling LVI damages by lowering the elastic material properties which allowed investigating the Lamb wave propagation at different stages of LVI damages evolution. The latter, proposed in this paper, conversely to the first one and the most of techniques presented in literature, consists of simulating Lamb wave propagation in a plate characterized by an initial stress-strain state and the related failures carried out by a previous impact simulation involving the same model. Such technique allows a better damage modelling and, consequently, overcoming the damage modelling approximations introduced by the former strategy; the lowering of the elastic material properties leads to a bad damage modelling which does not allow reproducing accurately what happens in the reality. Such procedure allowed investigating the Lamb wave propagation at different impact energy levels. The interaction between Lamb waves and damages has been investigated under three central frequencies of the actuation signal: 150 kHz, 200 kHz and 250 kHz which resulted in interesting observations to minimize the effect of the first lamina's fibres orientation on the wave propagation velocity. It is well known that different wave propagation velocities along fibres and matrix lead to different RMSD (Root Mean Square Deviation) damage index values, even if the sensors are mounted at the same distance from the damage location, resulting in wrong or less accurate information about the identification of both damage size and location during the post-processing phase. Moreover, the relationships between the RMSD damage index values, recorded at different instants of time of the impact history, and the impactor phases has been achieved. Finally a comparison between the results achieved by the two investigated strategies has been carried out and presented here.